THE LANDSCAPE OF EDUCATION IN THE UNITED STATES - Abduqaxxorov Diyorbek; Botirova Hakima (Лучшие интеллектуальные исследования, 2023)
Annotation: The article highlights the decentralized nature of the U.S. education system, where states have considerable autonomy in shaping curriculum and policies. This characteristic reflects the diversity in educational approaches across the country.The article acknowledges the pivotal role of standardized testing, such as the SAT and ACT, in the K-12 education system. This testing culture has implications for college admissions and shapes the academic trajectory for many students.